Innovation of the problem based learning model with contextual teaching learning in mathematics learning in the Industrial Revolution 4.0 era: A comparative case studies - Nining Hajeniati; Andi Kaharuddin (International Journal of Trends in Mathematics Education Research, 2022)
This study aims to compare learning outcomes, activeness, and students’ responses in learning mathematics in the era of the industrial revolution 4.0. Type of study is a quasi-experimental design with a pretest post-test only comparison design. The study population was the high school students in class XI with the samples consisting of three classes from different schools. The results of the descriptive and inferential analysis show that there were differences from the application of the three learning models which were then being tested by Tukey and they were depicted descriptively and inferentially that the combination model of Problem based learning setting Contextual teaching learning was more effective than the model of Problem based learning and Contextual teaching learning in terms of learning outcomes, activeness and student responses in the industrial revolution 4.0.